Analysis of influence factor of service quality and taxpayer satisfaction in reporting e-SPT - Nobertus Purnomo Lastu (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2023)
Tax Volunteers are college students assigned by the Directorate General of Taxes to assist in reporting Tax Returns (SPT) using the electronic Tax Return (e-SPT). Regarding to the services provided by tax volunteers, it is necessary to evaluate their performance. This study aims to analyze the factors that influence the service quality performed by the Tax Volunteers whether they have met the service quality and taxpayer satisfaction. The data obtained was processed using Importance Performance Analysis (IPA) with the help of Cartesian diagrams for service quality and to determine the level of taxpayer satisfaction using a Tao diagram on Customer Satisfaction Index analysis. Based on the findings, the service quality provided by Tax Volunteers in Surabaya is influenced by factors consisting of courtesy and reliabilities factors, while tangibles and serviceability still need to be improved. Meanwhile, the factors of reliability, competence, courtesy, security, accessibility, communication, and customer understanding are considered as good service quality, while the tangible and serviceability factors don’t affect service quality. The following analysis relates to taxpayer satisfaction, it was found that in general taxpayer satisfaction has been fulfilled because the interests or expectations of taxpayers are lower than the perception of performance obtained.